STUDY THE LEVELS OF ERYTHROFERRONE, UREA AND CREATININE IN CHRONIC KIDNEY DISEASE PATIENT IN KIRKUK CITY (Academia Science Repository, 2023)
The dysfunction of kidney functions is one of the most common diseases among people on a global scale. This disease can be classified as low levels of renal infiltration rate less than 60 ml/min. and the renal failure disease were divided into five stages that are evaluated through some important parameters, which include glomerular filtration rate, urea and creatinine levels in serum.